Cyclic distances of idempotent convolutional codes. (January 2021) - Gómez-Torrecillas, José; Lobillo, F.J.; Navarro, Gabriel
Abstract: We show that, for convolutional codes endowed with a cyclic structure, it is possible to define and compute two sequences of positive integers, called cyclic column and row distances, which present a more regular behavior than the classical column and row distance sequences. We then design an algorithm for the computation of the free distance based on the calculation of the cyclic column distance sequence.